Development of Guided Inquiry-Based Flipped Classroom Learning System Using Moodle on Buffer Solution Material for the Industrial Revolution 4.0 - Aprilia Silviani Harahap; Mawardi Mawardi (Universitas Lampung, 2022)
Abstract: Development of Guided Inquiry-Based Flipped Classroom Learning System Using Moodle on Buffer Solution Material for the Industrial Revolution 4.0. This research aimed to develop a guided inquiry-based flipped classroom learning system using moodle on buffer solution material and to test the validity and practicality of the learning system results. This conducted research isclassified by Educational Design Research with the Plomp development model. The subjects of this research were 3 teacher of the chemistry, and 20 students in class XII MIPA 3 at SMAN 8 Padang. The instrument used is a questionnaire of the validity and practicality of the developed learning system. The validity data were analyzed by Aiken's V formula while the practicality used the percentage method. The results of construct validation are 0.91 and the content validation are 0.86 in the valid category, while the practical results obtained from student responses and teacher's response are 94% in the very practical category. Based on the results of these studies indicate that the learning system developed is valid and practical. so, this learning system can be used as an alternative learning that support the industrial revolution 4.0 era. Keywords: Buffer Solution, Flipped Classroom, Guided Inquiry, Industrial Revolution 4.0. Abstrak: Pengembangan Sistem Pembelajaran Flipped Classroom Berbasis Inkuiri Terbimbing Menggunakan Moodle Pada Materi Larutan Penyangga Untuk Era Revolusi Industri 4.0. Penelitian ini bertujuan untuk mengembangkan sistem pembelajaran flipped classroom Berbasis inkuiri terbimbing menggunakan moodle pada materi larutan penyangga dan menguji kevalidan serta kepraktisan sistem pembelajaran yang dihasilkan. Jenis penelitian yang dilakukan adalah Educational Design Research dengan model pengembangan Plomp. Subjek penelitian ini adalah 3 orang guru kimia, dan 20 siswa kelas XII MIPA 3 SMAN 8 Padang. Instrumen yang digunakan adalah angket validitas dan praktikalitas sistem pembelajaran yang dikembangkan. Data Validitas dianalisis menggunakan rumus Aiken's V sedangkan praktikalitas menggunakan metode persentase. Hasil validasi konstruk sebesar 0,91 dan validasi isi sebesar 0,86 dalam kategori valid. Sedangkan hasil praktikalitas yang diperoleh dari respon peserta didik dan respon guru sebesar 94% dalam kategori sangat praktis. Berdasarkan hasil penelitian tersebut menunjukkan bahwa sistem pembelajaran yang dikembangkan sudah valid dan praktis. Sehingga sistem pembelajaran ini dapat dijadikan sebagai alternatif pembelajaran yang mendukung era revolusi industri 4.0. Kata kunci: Larutan Penyangga, Flipped Classroom, Inkuiri Terbimbing, Revolusi Industri 4.0. DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.11